TRANSANNULAR DIELS-ALDER REACTION OF A MACROCYCLIC TRIENE, (E,E,E)-13-TRIDECA-2,8,10-TRIENOLACTONE - JUNG, SH; LEE, YS; PARK, H; KWON, DS (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
(E,E,E)-13-trideca-2,8,10-trienolactone 3 undergoes rapid transannular Diels-Alder reaction to produce the trans-anti-cis tricyclic lactone 4 as a single cycloadduct.